2014
DOI: 10.1074/jbc.m114.588657
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy during Group B Streptococcus Infection of Blood-Brain Barrier Endothelium

Abstract: Background: Penetration of brain endothelium by Group B streptococcus (GBS) is the first step in the development of meningitis. Results: Autophagy is activated in response to GBS infection. Conclusion: Autophagy induction occurs through GBS toxin expression, while key autophagic proteins contribute to GBS destruction. Significance: Understanding the role of autophagy in brain endothelium may inform novel strategies to prevent the pathogenesis of bacterial meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 81 publications
(81 reference statements)
2
47
0
Order By: Relevance
“…For example, one study conducted by Eugenin et al examined the role of human immunodeficiency virus (HIV)-infected astrocytes in BBB disruption using a 2D Transwell model [201]. Another study described by Cutting et al examined selective autophagy activities in host defenses after BBB penetration of Group B Streptococcus (GBS), one of the leading meningeal pathogens, both in a 2D model and in vivo [202]. However, although many studies have been carried out using different in vitro BBB models, few studies have used this advantageous technology for brain infection studies.…”
Section: Bbb-on-a-chipmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study conducted by Eugenin et al examined the role of human immunodeficiency virus (HIV)-infected astrocytes in BBB disruption using a 2D Transwell model [201]. Another study described by Cutting et al examined selective autophagy activities in host defenses after BBB penetration of Group B Streptococcus (GBS), one of the leading meningeal pathogens, both in a 2D model and in vivo [202]. However, although many studies have been carried out using different in vitro BBB models, few studies have used this advantageous technology for brain infection studies.…”
Section: Bbb-on-a-chipmentioning
confidence: 99%
“…One of the underlying reasons for their limited use in this area may be due to the toxicity that results from co-culturing brain endothelial cells with infectious pathogens. With this, Brown et al introduced a BBB-on-a-chip microfluidic device consisting of separate vascular and brain channels, separated by a porous PDMS membrane [202]. This not only enables cell-to-cell interaction between brain tissue cells, but also allows for the independent perfusion of both compartments.…”
Section: Bbb-on-a-chipmentioning
confidence: 99%
“…In addition, infection of macrophages and epithelial cells with B. pseudomallei or Burkholderia cenocepacia leads to downregulation of certain autophagy genes, resulting in decreased levels of autophagy[39,40]. Group B streptococcus (GBS) induces autophagy during infection of EC, but still resides primarily in single membrane-bound compartments, suggesting that GBS evades targeting to autophagosomes[41]. Streptococcus suis blocks xenophagy during infection of macrophages by secreting superoxide dismutase to scavenge cellular ROS[42].…”
Section: Xenophagy Beyond M Tuberculosis As Revealed By Cell Culturementioning
confidence: 99%
“…The use of rapamycin in cell cultures has been shown to decrease the survival of various intracellular bacterial pathogens including GBS[41], P. aeruginosa [103], Salmonella [44], B. pseudomallei [104], and M. tuberculosis [105]. However, the differences in bacterial burden tend to be less than 2.5 fold[41,44,103,104]. In addition, a recent study found that in macrophages coinfected with HIV and M. tuberculosis , stimulation of autophagy with rapamycin actually led to increased M. tuberculosis survival[106].…”
Section: Targeting Autophagy As a Host-directed Therapy To Treat Bactmentioning
confidence: 99%
“…In another example, intracellular Group B Streptococcus β-hemolysin/cytolysin (β-h/c) triggers autophagy in ECs, which in turn kills the majority of the internalized bacteria [27]. Thus, in both of these examples ECs are able to fight back with autophagy, but not effectively enough to completely prevent disease.…”
Section: Autophagy: Endothelial Cells Fight Backmentioning
confidence: 99%